The Extent of Supplier and Customer Involvement in New Product Innovation - Araci, Zehra Canan (2013)
In recent decades, global competitive markets, rapid technological changes, and a demand for new products from customers have forced organisations to innovate state-of-the-art products that would be able to compete with their rivals. Otherwise, there is always a risk of losing competitiveness and motivation in order to remain in the market. Knowledge has an inevitable role in innovation since it facilitates idea creation and new product development processes. Companies are aware of the significance of managing innovation and knowledge all over the world. Successful innovation and knowledge management can enable companies to shine within their particular industries. Since these subjects are noticeable for academics and practitioners, there are numerous studies examining the role of internal and external knowledge in innovation. Although the vast majority claim that there are positive effects in involving external partners in innovation processes, a few researches have also mentioned the possible disadvantages. This study aims to investigate how important involving suppliers and customers in new product innovation activities is from a performance improvement’s point-of-view. Performance indicators are defined as: the number of new products, the speed at which new products are introduced, and the frequency of introducing new products. A likert scale questionnaire was conducted in India, with 200 manufacturers from different sectors participating in this survey. The responses were provided before this study was conducted. The data extracted from this questionnaire was analysed using the IBM SPSS 21 statistics software package. The hypotheses relevant to the aim and objectives of this research were established and tested using the Pearson correlation and multiple regression analysis. Significant findings have been achieved; i.e., that there is positive relation between building good relationships with both suppliers and customers and obtaining knowledge, though it is not a strong, but rather a moderate, correlation. Additionally, it was found that supplier and customer knowledge has several benefits for the innovation activities of the companies surveyed. Moreover, the positive effects of supplier and customer involvement in product innovation performance were investigated. Consequently, it can be suggested that, if organisations involve their key suppliers and customers in their product development processes, they will be able to enhance their innovation abilities and improve the performances of introducing even more new products, both more quickly and more often.